The value of internal sources of funding liquidity: U.S. broker-dealers and the financial crisis - Cecilia Caglio; Adam Copeland; Antoine Martin (Federal Reserve Bank of New York, 2021)
We use confidential and novel data to measure the benefit to broker-dealers of being affiliated with a bank holding company and the resulting access to internal sources of funding. We accomplish this by comparing the balance sheets of broker-dealers that are associated with bank holding companies to those that are not and we find that the latter dramatically re-structured their balance sheets during the 2007-09 financial crisis, pivoting away from trading illiquid assets and toward more liquid government securities. Specifically, we estimate that broker-dealers that are not associated with bank holding companies both increased repo as a share of total assets by 10 percentage points and also increased the share of long inventory devoted to government securities by 15 percentage points, relative to broker-dealers associated with bank holding companies.
Keywords: G2; G21; G23; 330; broker-dealers; shadow banking; liquidity risk; repo market